Análise do efeito hemodinâmico agudo pós-exercício em diferentes métodos de treinamento em atletas de powerlifiting paralímpico - Jesus, Joseane Barbosa de (2022)
Introduction: Paralympic powerlifting (PP) is one of the sports modalities that use strength training with high loads, causing various physiological responses, resulting from metabolic and hemodynamic adaptations. These physiological responses can occur through changes in heart rate (HR), blood pressure (BP), among others, which can be used as training evaluation parameters. Objective: To evaluate hemodynamic responses after traditional (TT) and eccentric (ET) training sessions in PP athletes. Methods: The sample consisted of 12 male PP athletes of national level (30.8 ± 10.05 years old; 70.0 ± 16.1 kg), with at least 1 year of experience and officially classified by the Paralympic Committee Brazilian (CPB). After determining the training load through the 1RM test, the athletes underwent a training session on different days. Five sets of five repetitions (80% – 1RM) and ET five sets of five repetitions were used in the TT (load in the eccentric phase of 110% and in the concentric phase 80% of 1RM). Blood pressure (BP), heart rate (HR), double product (DP) and myocardial oxygen volume (MVO2) were measured before training, immediately after, and at 5', 10', 20', 30', 40', 50', 60' and 24h after each session. Results: It was found that there were no significant differences in relation to blood pressure, systolic, diastolic and mean, respectively, between the training conditions, traditional and eccentric, but there was a clinically noticeable reduction in relation to the eccentric method. The clinical values found show a reduction of 6.0 and 6.5 mmHg in SBP when compared with rest at 60' and 24h, respectively. There was also a reduction in MAP by 2.0 and 2.3 mmHg when compared with rest at 60' and 24h, in relation to the same method. Compared to baseline, heart rate was significantly elevated at various times in the ET, before and 20 minutes (“a” p=0.023), 40 minutes (“b” p=0.035), but decreased to baseline in 24 minutes. hours (“c” p=0.043, η2p=0.395). In addition, the double product in the ET decreased at 60 minutes (“c” p=0.042) and 24 hours (“d” p=0.043). A significant reduction in myocardial oxygen volume was found in the ET at 24 hours (“g” p=0.018; η2p=0.393, high effect). Conclusion: a session of the traditional and eccentric training methods can be effective to cause significant changes in the cardiovascular system and the application of the methods did not present a risk of hemodynamic overload for PP athletes and that the methods also did not promote a statistically significant hypotensive effect, however, according to the absolute values found, this effect should be clinically considered.